Impact of Clinical Pharmacist-led Interventions on the Outcomes of Patients with Bipolar I Disorder: A Randomized Clinical Trial - Nazanin Gorgzadeh; Niayesh Mohebbi; Kheirollah Gholami; Homayoun Amini; Ali-Akbar Nejatisafa; Jamshid Salamzadeh (Journal of Research in Pharmacy Practice)
Objective: Poor medication adherence, drug interactions, and adverse drug events occur frequently in patients with bipolar I disorder (BD-I), affecting their treatment outcomes. Due to limited research regarding the impact of pharmaceutical care (PC) services in the management of patients with BD-I, this study was designed to assess the role of clinical pharmacist-led interventions on outcomes of BD-I patients. Methods: A prospective randomized clinical trial was designed, and 59 patients were randomly assigned to the intervention group and 48 patients to the control group. Patients in the intervention group were provided with medication therapy management and follow-up services by the clinical pharmacist, whereas the control group only received routine care. Outcomes which were assessed at baseline (before discharge), 1 month, and 3 months after discharge were the Medication Appropriateness Index (MAI), Beck Depression Inventory-II (BDI-II), Young Mania Rating Scale, and World Health Organization Quality of Life, Brief version (WHOQOL-BREF). Findings: Endpoint mean changes in MAI scores from baseline were −5.25 ± 5.19 and 2.02 ± 3.98 points for the intervention and control groups, respectively (P < 0.001). Depressive symptoms, measured by the BDI-II, also showed significant improvement in the intervention group; the mean change from baseline to 2nd follow-up assessment was −1.47 ± 7.73 in the intervention group and 1.66 ± 6.42 in the control group (P = 0.02). Furthermore, the mean change from baseline to 2nd follow-up in the psychological health domain of the WHOQOL-BREF questionnaire was significantly higher in the intervention group (4.59 ± 17.79) compared with the control group (−3.90 ± 12.55) (P = 0.005). Conclusion: Our findings reveal that clinical pharmacist-provided services could positively affect outcomes in BD-I patients.